Implementation of Fish Farming in Buckets To Improve Softskill Teachers and Students In SMP N 4 Rantau Panjang, Ogan Ilir Regency - Khotimah, Khusnul; Helmizuryani, Helmizuryani; Muslimin, Boby; Sari, Meika Puspita; Harmilia, Elva Dwi; Suyatno, Suyatno; Yani, Ade Vera; Ma’ruf, Irkhamiawan (Altifani Journal: International Journal of Community Engagement, 2021)
Fish farming in buckets or more popularly known as BUDIKDAMBER cultivates fish and vegetables in one bucket. In addition to increasing students' understanding of ecosystems, BUDIKDAMBER can also be a solution for teachers and students who have limited land for plant and fish cultivation. This activity aims to provide education and training to teachers and students regarding fish farming techniques currently used to solve small-scale fish farming. The implementation of this activity includes the preparation stage, the material delivery stage, and the experimental stage. Through soft skills training, it can increase knowledge and insight for teachers and students at SMPN 4 Rantau Panjang regarding the BUDIKDAMBER technique so that it is to motivate and attract teachers and students to try at home and pass on the knowledge gained to the surrounding community